Children with transient loss of consciousness: Clinical characteristics and the effectiveness of diagnostic tests - Young Ju Choi; Mi Young Han; Eun Hye Lee (Pediatrics and Neonatology)
Background: Transient loss of consciousness (TLOC) is common among children and adolescents. The aims of this study were to identify clinical differences between patients with vasovagal syncope and those with epileptic seizures, which account for a large proportion of TLOC cases, and to evaluate the effectiveness of various diagnostic tests. Methods: The medical records of 160 children and adolescents with TLOC were analyzed retrospectively, and age, sex, clinical symptoms, and trigger factors were recorded. The cardiological and neurological evaluations performed included electrocardiograms, computed tomography scanning, magnetic resonance imaging, electroencephalograms (EEGs), echocardiograms, and head-up tilt tests (HUTTs). Overall assessments of the 160 patients generated final diagnoses. Results: The mean age of patients was 14.6 years old and TLOC occurred more frequently among girls (59.4%). The most common final diagnosis was vasovagal syncope (n = 102, 63.4%), followed by undetermined (n = 21, 13.1%) and epileptic seizures (n = 17, 10.6%). There were many other diagnoses, including cardiogenic syncope (1.3%). Patients diagnosed with vasovagal syncope were much more likely to have dizziness or light-headedness and blurred vision as pre-symptoms (p < 0.05), whereas patients diagnosed with epileptic seizures were more likely to have convulsions as an accompanying sign (p < 0.05). In addition, standing up was the most significant trigger factor for TLOC among those diagnosed with vasovagal syncope (p < 0.05). The sensitivity, specificity, and accuracy of the HUTT for vasovagal syncope were 95.1%, 75.0%, and 91.8%, respectively. Similarly, the sensitivity, specificity, and accuracy of EEGs for epileptic seizures were 80.0%, 70.6%, and 80.0%, respectively. Conclusion: Vasovagal syncope and epileptic seizures should be considered as possible causes of most cases of TLOC in children and adolescents. An accurate case history and appropriate evaluation are essential for correct diagnoses.